Draft Universal Credit (Managed Migration) Regulations 2018 (SI 2018/****) : Report by the Social Security Advisory Committee under Sections 172(1) and Section 174(1) of the Social Security Administration Act 1992 and statement by the Secretary of State for Work and Pensions in accordance with Section 174(2) of that Act.: Report by the Social Security Advisory Committee under Sections 172(1) and Section 174(1) of the Social Security Administration Act 1992 and statement by the Secretary of State for Work and Pensions in accordance with Section 174(2) of that Act. (2018) - Unknown
No abstract available